Oxidative Stress and the NLRP3 Inflammasome: Focus on Female Fertility and Reproductive Health - Efthalia Moustakli; Sofoklis Stavros; Periklis Katopodis; Charikleia Skentou; Anastasios Potiris; Periklis Panagopoulos; Ekaterini Domali; Ioannis Arkoulis; Theodoros Karampitsakos; Eleftheria Sarafi; Theologos M. Michaelidis; Athanasios Zachariou; et al. (Cells)
Chronic inflammation is increasingly recognized as a critical factor in female reproductive health; influencing natural conception and the outcomes of assisted reproductive technologies such as in vitro fertilization (IVF). An essential component of innate immunity, the NLR family pyrin domain-containing 3 (NLRP3) inflammasome is one of the major mediators of inflammatory responses, and its activation is closely linked to oxidative stress. This interaction contributes to a decline in oocyte quality, reduced fertilization potential, and impaired embryo development. In the ovarian milieu, oxidative stress and NLRP3 inflammasome activation interact intricately, and their combined effects on oocyte competence and reproductive outcomes are significant. The aims of this review are to examine these molecular mechanisms and to explore therapeutic strategies targeting oxidative stress and NLRP3 inflammasome activity, with the goal of enhancing female fertility and improving clinical outcomes in reproductive health.